Алелопатичні особливості ароматичних рослин родини Lamiaceae Lindl. - Kotyuk, L.A.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
Allelopathic features of 13 aromatic plants of Lamiaceae Lindl. family are studied. Dracocephalum moldavica L., Lavandula vera D.C. and Lophanthus anisatus Adans. are showed the highest phytotoxic effect of aqueous extracts of lifetime emissions of aromatic plants relative to Triticum aestivum Linn., which reduced germination rates, respectively, by 15.6; 4.9 and 1.7 times. Extracts of plant material of Nepeta transcaucasica Grossh showed the stimulating effect, while germination of wheat was around 96.3 % versus 86.0 % on control. Hyssopus officinalis L. and Dracocephalum moldavica resulted in inhibition of growth processes in Zea mays L. by 1.8–2.6 times. Stimulating effect on Zea mays seed (2 to 6%) was found in Salvia sclarea L., S. officinalis L. and Elsholzia cristata Willd. Hyssopus officinalis, Monarda didyma L. and Dracocephalum moldavica are showed the highest phytotoxic effect of aqueous extracts of remains of aromatic plants relative to Triticum aestivum, which reduced germination rates, respectively, by 2.6; 2.0 and 1.8 times. Lophanthus anisatus, Dracocephalum moldavica and Lavandula vera resulted in inhibition of growth processes in Zea mays by 1.7; 1.5 and 1.4 times.